The synergistic justification of the language system versus Aristotle’s scientific picture - Kairzhanov, Abay K.; Karlygash Sarekenova, Raikhan Tuxaitova,; Galimullina, Alfiya F.; Kussainova, Raisa E. (Opción, 2020)
The article is devoted to the study of the scientific picture of the world against the backdrop of ancient times. To analyze the language system, we used the methodology of cognitive science and synergetic. The work reveals that the language system, undergoing synergy (according to Aristotle, the movement is subject to certain obstacles and the thing finds its natural place on its movement), is a process of interaction of two interconnected and contradictory principles - generation and dissipation. In conclusion, to describe the scientific (linguistic) picture of the world, it is necessary to use a convergent approach in an attempt